Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/tid.13078
|View full text |Cite
|
Sign up to set email alerts
|

Impact of direct‐acting antivirals for hepatitis C virus therapy on tacrolimus dosing in liver transplant recipients

Abstract: Introduction Direct‐acting antivirals (DAAs) have transformed hepatitis C virus (HCV) management post‐liver transplant. As HCV clears during DAA treatment, hepatic metabolism improves, resulting in decreased tacrolimus concentrations that may require dose adjustment. The purpose of this study was to determine appropriate management of immunosuppression in liver transplant recipients during and following treatment of HCV. Methods This study was a single‐center retrospective analysis of 71 liver transplant recip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…However, another study observed a significant decrease of trough Tac levels throughout the course of therapy, especially during the first month [14]. Bixby et al [21] also found a great decrease of Tac concentration in the first 4 weeks of DAAs therapy and stable levels thereafter in a liver transplant cohort. Our study reviewed 7 patients with stable trough Tac levels before and after 4 weeks during DAAs therapy, without any dose adjustment, which revealed a different result from part of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, another study observed a significant decrease of trough Tac levels throughout the course of therapy, especially during the first month [14]. Bixby et al [21] also found a great decrease of Tac concentration in the first 4 weeks of DAAs therapy and stable levels thereafter in a liver transplant cohort. Our study reviewed 7 patients with stable trough Tac levels before and after 4 weeks during DAAs therapy, without any dose adjustment, which revealed a different result from part of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the majority of clinical data evaluating the impact of DAAs on tacrolimus pharmacotherapy is confined to the liver transplant population. Several of these studies have in fact found transplant recipients required higher doses of tacrolimus to achieve similar levels after completing therapy with DAAs 16,17 . While useful, this information may not apply to recipients of non–liver transplants because it is hypothesized that changes in tacrolimus dose requirements are due to resolution of HCV infection rather than a drug‐drug interaction 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Another concern regarding the use of DAA during the course of HCT is the possible interaction with the drugs used for GVHD prophylaxis 15,16 . There is lack of data on the drug‐drug interaction between Sof‐Vel and calcineurin inhibitors or mTOR inhibitors.…”
Section: Discussionmentioning
confidence: 99%